2019
DOI: 10.1002/imhj.21822
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal attachment and early childhood emotional, behavioral, and developmental characteristics: A longitudinal study

Abstract: This study examines the associations between prenatal attachment and child development, socioemotional behavioral problems, and competence at early childhood. It also inquires whether maternal depression and anxiety at the prenatal period and at early childhood are associated with child outcomes. The study consisted of 83 mothers and their children. Data regarding the prenatal attachment, depression, and anxiety were collected during Weeks 28 to 40 of gestation. When the children were 21 to 31 months old, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
0
19
1
1
Order By: Relevance
“…While the association between maternal–fetal attachment and infant adaptive behavior has not previously been studied, this finding corroborates other research whereby poorer maternal–fetal attachment was associated with maternal-rated infant outcomes such as global developmental delay [ 13 ], less optimal infant temperament [ 10 ], colic [ 11 ], and decreased sleep [ 12 ]. In contrast with a study by Arguz Cildir, Ozbek, Topuzoglu, Orcin and Janbakhishov [ 14 ], in which maternal–fetal attachment was associated with infant/child behavioral and emotional competence, our study revealed no significant association between attachment and the social-emotional scale. While both studies used maternal-report, infants in the present study were slightly younger, and different infant developmental assessments were used; however, further research is required.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While the association between maternal–fetal attachment and infant adaptive behavior has not previously been studied, this finding corroborates other research whereby poorer maternal–fetal attachment was associated with maternal-rated infant outcomes such as global developmental delay [ 13 ], less optimal infant temperament [ 10 ], colic [ 11 ], and decreased sleep [ 12 ]. In contrast with a study by Arguz Cildir, Ozbek, Topuzoglu, Orcin and Janbakhishov [ 14 ], in which maternal–fetal attachment was associated with infant/child behavioral and emotional competence, our study revealed no significant association between attachment and the social-emotional scale. While both studies used maternal-report, infants in the present study were slightly younger, and different infant developmental assessments were used; however, further research is required.…”
Section: Discussioncontrasting
confidence: 99%
“…As indicated in a systemic review by Branjerdporn et al [ 9 ], maternal–fetal attachment has been shown to influence a range of maternal-reported infant outcomes, such as temperament [ 10 ], colic [ 11 , 12 ], and developmental delay [ 13 ]. More recently, a Turkish study by Arguz Cildir et al [ 14 ] revealed that maternal–fetal attachment was associated with maternal-reported infant behavioral and emotional competence, and development when infants were 21–31 months old. Similarly, a recent Palestinian study [ 15 ] with 12-month old infants showed that maternal–fetal attachment in mothers with significant war trauma predicted maternal-reported infant sensorimotor and fine motor skill development using the Minnesota Child Development Inventory [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions aimed at reducing depressive symptoms that can occur during the gestational period and that can impact the psychological wellbeing of expectant parents and the development of a positive prenatal attachment should be implemented [155][156][157][158][159][160]. To enhance this bond takes on a main role, considering its further influence on postnatal depression (as most of the studies included in the current systematic review reported) [74,81,99,105,110,111], and on other important factors involved in the wellbeing of the both parents and the child [28,29,[32][33][34][35]37,38,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors underline that low maternal prenatal attachment is associated with low prenatal maternal fetus representations and self-care [25][26][27][28][29] and low postnatal attachment until 24 months postpartum [30][31][32][33][34][35][36][37][38][39]. Additionally, poor parental prenatal attachment has been connected to behavioral and conduct problems, lower cognitive development, and negative socioemotional regulations in early childhood [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The literature investigating pre-natal attachment was more focused on its predictors rather than its consequences (Damato, 2004;Cannella, 2005;Hjelmstedt et al, 2007;Bielawska-Batorowicz and Siddiqui, 2008;Yarcheski et al, 2009;Ossa et al, 2012;Della Vedova and Cristini, 2019;Tichelman et al, 2019). Nonetheless, several studies highlighted the predictive role of pre-natal attachment on the child's socioemotional, behavioral and cognitive development in early childhood and the parent's mental health during the perinatal period (Misri and Kendrick, 2008;Yarcheski et al, 2009;Alhusen et al, 2013;Della Vedova, 2014;Walsh et al, 2014;Branjerdporn et al, 2017;Cildir et al, 2019;Rollè et al, 2020).…”
Section: Introductionmentioning
confidence: 99%